PERFORMANSI JARINGAN CODE DIVISION MULTIPLE ACCESS (CDMA) MENGGUNAKAN MOBILE PHONE JAMMER - Prijono, Wahyu Adi (Fakultas Teknik Universitas Wisnuwardhana, 2020)
The use of communication tools in some places can be disturb to many people, for example in place of worship and a meeting room. It can be prevented by using a device called a mobile phone jammer. Use of Mobile Phone Jammer can jamming the mobile station signals (CDMA and GSM) both uplink and downlink with the workings of the mobile phone jammer issuing signal with a frequency that is similar to the mobile station, however the power emitted is greater. The research will be discussed on the placement of the mobile phone jammer in the room. With two is the parameter is repeater and without repeater. In primary data capture method does is method of spectrum analyzer and method of walktest. On walktest software used is tems investigation 8.0.3 for retrieval of data with the parameter of quality a signal ( Ec / Io , FFER , RSSI , TxPo , and TxGa ) and MapInfo as logfile processing results of TEMS Investigation which can show the maximum range where the mobile station can be jamming. Based on measurements with the method of spectrum analyzer, power mobile phone jammer has power – 74,6 dB and by using mathematical calculations obtained range 43 m. On measurement method using walktest, the first parameter is the chosen location without repeaters the maximum range the jammer by 17 metres and with power jammer effective registration -62.9 dB. Whereas, in the location parameter contained repeater the maximum range jammer obtained is 10 meters and power jammer effective 60,2 dB.